THE IMPACT OF IMMERSIVE VIRTUAL REALITY (VR) ON SCIENCE COMPREHENSION AND ENGAGEMENT IN PRIMARY SCHOOL STUDENTS - Sanchez, Pedro; Gonzalez, Maria; Martinez, Juan (International Journal of Educatio Elementaria and Psychologia, 2025)
Immersive Virtual Reality (VR) has gained increasing attention in educational settings as a tool to enhance learning experiences. Its ability to create interactive and engaging environments has shown promise, particularly in science education. This study examines the impact of immersive VR on science comprehension and engagement among primary school students. The research explores whether VR can provide an effective platform for teaching scientific concepts and improving student participation in science learning. The study utilized a quasi-experimental design, where two groups of primary school students participated in either VR-based science lessons or traditional, textbook-based lessons. Data was collected through pre- and post-tests to measure comprehension, along with surveys to assess student engagement levels. The findings indicate that students who engaged with VR-based lessons showed a significant improvement in science comprehension compared to their counterparts in the traditional group. Additionally, VR participants reported higher levels of engagement and interest in science subjects, suggesting that immersive experiences can enhance students’ motivation and participation in learning. This study concludes that immersive VR has the potential to revolutionize science education by fostering deeper understanding and increasing student engagement, making it a valuable tool for the future of teaching and learning in primary schools.